Symptom perception in heart failure – Interventions and outcomes: A scoping review. (April 2021) - Santos, Gabrielle Cécile; Liljeroos, Maria; Dwyer, Andrew A.; Jaques, Cécile; Girard, Josepha; Strömberg, Anna; Hullin, Roger; Schäfer-Keller, Petra
Abstract: Background: Symptom perception in heart failure has recently been described as essential in the self-care process bridging self-care maintenance and self-care management. Accordingly, symptom perception appears to be critical for improving patient outcomes such as decreased hospital readmission and increased survival. Objectives: To explore what interventions have been reported on heart failure symptom perception and to describe outcomes responsive to symptom perception. Design: We conducted a scoping review using PRISMA Extension for Scoping Reviews. Data sources: Structured searches of Medline, PubMed, Embase, CINAHL, PsychINFO, Web of Science, Cochrane, Joanna Briggs Institute and Grey literature databases. Review methods: Two authors independently screened references for eligibility. Eligible articles were written in English, French, German, Swedish, Italian or Spanish and concerned symptom perception in adults with heart failure. Data were extracted and charted in tables by three reviewers. Results were narratively summarized. Results: We identified 99 eligible studies from 3055 references. Seven interventional studies targeted symptom perception as the single intervention component. Mixed results have been found: while some reported decreased symptom frequency, intensity and distress, enhanced health-related quality of life, improved heart failure self-care maintenance and management as well as a greater ability to mention heart failure symptoms, others found more contacts with healthcare providers or no impact on anxiety, heart failure self-care nor a number of diary reported symptoms. Additional interventional studies included symptom perception as one component of a multi-faceted intervention. Outcomes responsive to symptom perception were improved general and physical health, decreased mortality, heart failure decompensation, as hospital/emergency visits, shorter delays in seeking care, more consistent weight monitoring, improved symptom recognition as well as self-care management, decreased hospital length of stay and decreased costs. Conclusions: While many studies allowed to map a comprehensive overview of interventions supporting symptom perception in heart failure as well as responsiveness to outcomes, only a few single component intervention studies targeting symptom perception have been reported and study designs preclude assessing intervention effectiveness. With regard to multiple component interventions, the specific impact of symptom perception interventions on outcomes remains uncertain to date. Well-designed studies are needed to test the effectiveness of symptom perception interventions and to elucidate relationships with outcomes.